2018
DOI: 10.1002/fsn3.710
|View full text |Cite
|
Sign up to set email alerts
|

The physiochemical properties and shelf‐life of orange‐fleshed sweet potato puree composite bread

Abstract: Value addition of orange‐fleshed sweet potato (OFSP) increases diversified utilization of this crop, which is rich in provitamin A carotenoids. OFSP bread, in which 30%–45% of wheat flour is replaced with OFSP puree, has been successfully commercialized in Kenya. However, the effect of this substitution on the bread's physiochemical properties and its shelf‐life are currently unknown. This study was designed to determine the physiochemical properties and shelf‐life of OFSP puree‐wheat flour composite bread (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 34 publications
7
37
1
Order By: Relevance
“…Liu et al (2016) reported that specific volume of steamed bread was decreased as PF increased from 0 per cent to 35 per cent, which were due to that wheat gluten was diluted by higher addition of PF. Wanjuu et al (2018) indicated that the specific volume of bread added with sweet PF was significantly lower than that of wheat bread, this might be owed to the reduced extensibility of wheat gluten which induced by the partial replacement of sweet PF. In addition, Bindvi et al (2017) indicated that sponge cake supplemented with 20 per cent mushroom powder exhibited decreased specific volume, which also might be due to the poor expansion and air holding characteristics of the mushroom powder.…”
Section: Resultsmentioning
confidence: 99%
“…Liu et al (2016) reported that specific volume of steamed bread was decreased as PF increased from 0 per cent to 35 per cent, which were due to that wheat gluten was diluted by higher addition of PF. Wanjuu et al (2018) indicated that the specific volume of bread added with sweet PF was significantly lower than that of wheat bread, this might be owed to the reduced extensibility of wheat gluten which induced by the partial replacement of sweet PF. In addition, Bindvi et al (2017) indicated that sponge cake supplemented with 20 per cent mushroom powder exhibited decreased specific volume, which also might be due to the poor expansion and air holding characteristics of the mushroom powder.…”
Section: Resultsmentioning
confidence: 99%
“…The results for the color of the plain bread are shown in Table 2 . The value for the letter L ∗ indicates changes in brightness or lightness [ 35 ]. The addition of purple yam flour caused low L ∗ value, which indicated that the plain bread was getting darker in color.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier finding by Wanjuu et al . (2018) indicated that a higher proportion of OFSP purée increases the smoothness of the crumbs, suggesting that the proportions can be adjusted so that more OFSP purée is used than the current 43%. Thus, increasing the proportion of OFSP purée in the bread would have both functional, nutritional and economic benefits, the latter arising from foreign exchange savings as Kenya is a net wheat importer.…”
Section: Resultsmentioning
confidence: 99%